Food Prices and the Multiplier Effect of Trade Policy - Giordani, Paolo (IMF Working Papers; Working Paper ;, 2014)
This paper studies the relationship between trade policy and food prices. We show that, when individuals are loss averse, governments may use trade policy to shield the domestic economy from large food price shocks. This creates a complementarity between the price of food in international markets and trade policy. Specifically, unilateral actions give rise to a "multiplier effect": when a shock drives up the price of food, exporters respond by imposing restrictions while importers wind down protection, thus exacerbating the initial shock and soliciting further trade policy activism. We test the key prediction of the theory with a new dataset that comprises monthly information on trade measures across 77 countries and 33 food products for the period 2008-11, finding evidence of a multiplier effect in food trade policy. These findings contribute to inform the broader debate on the proper regulation of food trade policy within the multilateral trading system.